2002
DOI: 10.1128/aem.68.9.4364-4369.2002
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Exopolysaccharides on Phage-Host Interactions in Lactococcus lactis

Abstract: In this study, we report that Lactococcus lactis strains producing exopolysaccharides (EPSstrains were insensitive to these phages. The monosaccharide composition of the polymer produced by the seven Eps ؉ strains was determined. The EPS produced by strains MLT3, SMQ-419, and SMQ-575 contained glucose, galactose, and rhamnose. The EPS fabricated by H414 contained only galactose. The EPS made by MLT2, SMQ-420, and SMQ-461 contained glucose and galactose. These findings indicate that the sugar composition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 42 publications
(35 reference statements)
2
51
0
Order By: Relevance
“…We also recently reported that the EPS-producing S. thermophilus strain MR-1C and its EPSnegative derivative were both sensitive to the same three pactype phages (7). Several phages can also infect EPS-producing Lactococcus lactis strains (21). Taken together, these results clearly indicate that the production of EPS does not confer potent protection against phage infections.…”
Section: Discussionsupporting
confidence: 50%
“…We also recently reported that the EPS-producing S. thermophilus strain MR-1C and its EPSnegative derivative were both sensitive to the same three pactype phages (7). Several phages can also infect EPS-producing Lactococcus lactis strains (21). Taken together, these results clearly indicate that the production of EPS does not confer potent protection against phage infections.…”
Section: Discussionsupporting
confidence: 50%
“…Finally, as the data shown in Table 2 indicate, the unique sucrose-derived glucan polymers produced by S. mutans do not significantly interfere with phage adsorption or replication. These data support the view that the production of polysaccharides does not confer a significant phage resistance phenotype (8,13,45).…”
Section: Resultssupporting
confidence: 79%
“…1b). The existence of an EPS matrix, contrary to previous hypotheses (16), was confirmed by in situ observations using CLSM. Figure 2a shows a loosened structure in which the bacteria were quasi-monodispersed and embedded in a continuous extracellular matrix that held the cells in position.…”
Section: Resultsmentioning
confidence: 47%